The genus Eurysternus Dalman, 1824 (Coleoptera: Scarabaeidae: Oniticellini) from Loreto department, Peru - Figueroa, Luis (2021)
Thirteen species of the genus Eurysternus (Coleoptera: Scarabaeidae: Oniticellini) occurring in Loreto Department - Peru are presented. Eurysternus ventricosus Gill, 1990 is recorded for the first time in Peru. Additionally, the habitus and aedeagus are illustrated, and distribution records for all the species found in the department are presented.